Impacto del sistema de costos en la rentabilidad de la imprenta gráficas nuevo mundo del cantón Latacunga, provincia de Cotopaxi - Guerrero Cajamarca, Sara Abigail (2017)
The following project research is aimed to establish an impact of cost System in the profitability of printing “Gráficas Nuevo Mundo" Company in the city of Latacunga, Cotopaxi Province, in order to set alternative solutions. Will track in managing cost in printing presses and the disadvantage that carries not having to face of the wide demand for competition in the market. The project will show a great assistance for making decision that focuses on the correct allocation and control of production costs, establishing an accurately register costs of each product, leaving aside the hand working, to contribute the performance of available resources and achieve a profitability for economic growing and local location in the cantonal, provincial and national market. Through the research carried out at the printing press showed that it does not have a cost system for managing of inventories. In addition to obtain feasible information were used interviews techniques, the observation was made to the manager as well, with the information collected made and analysis, it helps to establish if it is achievable to implement a cost system done by order productions, this one Will provide reliable information for the successful making decision process that leads to the growth and development of the printing press "Gráficas Nuevo Mundo".